Relationship between Social Media and Investment Decisions in the Nepali Stock Market - Khadka, Suresh; Chapagain, Bal Ram (The Spectrum, 2023)
The growing pervasiveness and influence of social media in different spheres of life cannot be denied at all. In this light, this study aims to examine the relationship between different aspects of social media and investment decisions in the context of the Nepali stock market. The study sample included 384 retail investors, and the data was collected through structured questionnaires. Descriptive statistics, Pearson correlation, and standard multiple regression analyses were used to analyze the data. Although significantly positive relationships were found between all aspects of social media and investment decisions, content on social media has a stronger relationship with investment decisions relative to the online community behavior on social media and corporate image on social media. This is among the limited studies of its kind in the distinct socio-economic context of Nepal. Corporate managers may regularly update relevant information on their social media platforms for attracting potential investors and increase their firm value. Likewise, regulators may run investor education programs in order to protect investors, particularly immature retail investors, from the risk associated with potentially less reliable information on social media platforms. Future researchers may employ a mixed-method research design to uncover the comprehensive set of factors influencing investment decisions in the context of the Nepali stock market.